Сравнительный анализ асимметричных алгоритмов NTRU, RSA И ECC - Бубырь, А. П.; Заросилова, М. Г. (ХНУРЭ, 2011)
This work is devoted to a comparative analysis of lattice-based public key algorithm NTRU and systems based on integer factorization (RSA) and the elliptic curve discrete log problem (ECC). Durability and speed of encryption/decryption operations were assessed. Conclusions about the advantages and disadvantages of the discussed cryptographic algorithms are given.
Keywords: асимметричный алгоритм; криптосистема